Association between subclinical left ventricular ejection fraction and platelet-to-lymphocyte ratio in patients with peritoneal dialysis - Duan, Yingjie; Peng, Zhong; Zhong, Shuzhu; Huang, Hong; He, Zhangxiu (Frontiers in Medicine, 2022)
Abstract Background: Reduced left ventricular ejection function (LVEF) was associated with increased mortality in peritoneal dialysis (PD) patients. Neutrophil-to-lymphocyte ratio (NLR) or platelet-to-lymphocyte ratio (PLR) was related to LVEF during PD. However, rare information is about relationship between monocyte-to-lymphocyte ratio (MLR) and LVEF, and usefulness of NLR, PLR, and MLR in predicting left ventricular systolic dysfunction (LVSD) in PD patients. Methods: All 181 PD patients were enrolled between 2014 and 2021 from the Nephrology Department of The First Affiliated Hospital of University of South China. Demographic features, clinical characteristics, laboratory values, and echocardiographic parameters were collected. Results: Mean age of the PD patients was 47.4 ± 12.6 and 90 (49.7%) were male. LVEF showed a negative correlation with PLR (r = -0.200, p = 0.007) and MLR (r = -0.146, p = 0.049). The levels of NLR, PLR, and MLR were increased in PD patients with LVSD compared with those in non-LVSD (all p＜0.05). PLR (OR 4.331, 95% CI: 1.223, 15.342), and albumin (OR 13.346, 95% CI: 3.928, 45.346) were significantly associated with LVSD PD patients in multivariate logistic analysis. For differentiating PD patients with LVSD, optimal cutoffs of NLR, PLR, MLR, and albumin were 4.5 (sensitivity: 76.7%, specificity: 55.0%, and overall accuracy: 58%), 202.6 (sensitivity: 66.7%, specificity: 69.5%, and overall accuracy: 69%), 0.483 (sensitivity: 53.3%, specificity: 72.8%, and overall accuracy: 30%), 34.6 (sensitivity: 72.2%, specificity: 66.7%, and overall accuracy: 69%), respectively. Conclusions: Our results revealed that PLR was better than NLR, MLR, and albumin in predicting LVSD in PD. Key words: platelet-to-lymphocyte (PLR); left ventricular ejection function (LVEF); peritoneal dialysis.